Efficient Replantation: Techniques, Tricks, and Secondary Procedures for Improved Functional Outcomes - Deborah B. Martins, MD; Ogi Solaja, MD; Gregory Buncke, MD (Journal of Hand Surgery Global Online)
Successful digit replantation is dependent on multiple factors, including patient demographics, comorbidities, the mechanism of injury, and the skill and experience of the surgical team and microsurgery center. Although patient and injury characteristics cannot be controlled, the microsurgeon can incorporate specific techniques to improve efficiency and optimize outcomes. Replantation can be tedious, and minimizing surgeon fatigue is important. This article aims to review strategies and tricks to increase efficiency and success in digit replantation, while also reviewing postreplant rehabilitation and secondary surgeries to optimize hand function.